Fungsi Kesenian Barongsai Pada Masyarakat Tionghoa di Kecamatan Payung Sekaki Pekanbaru Provinsi Riau - Fakhri Novriandy Simanjuntak; Idawati Idawati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This research aims to determine the function of the Barongsai art in the Chinese community in Payung Sekaki District, Riau Province. The theory used in this research is the theory of Allan P Merriam (1964:219:227) which states that art has functions, namely 1) communication function 2) entertainment function 3) symbolic function 4) function of integrating society. The method used in this research is descriptive analysis using qualitative data, with data collection techniques namely observation, interviews and documentation techniques. The subjects in this research were 4 people. The communication function of the lion dance art in Payung Sekaki District can be seen through the movements and appearance of the lion dance and the performers. Wushu martial arts movements and costumes from performers and lion dance. The entertainment function of the Lion Dance art in Payung Sekaki District is not only performed during Chinese New Year holidays, but also other events such as wedding parties, company inaugurations, and welcoming guests. The symbolic function of Barongsai art in Payung Sekaki District can be seen from several symbols of the Barongsai, such as the symbol of courage and strength marked by the beard on the Barongsai's chin and the symbol of prosperity and good luck marked by the ears and tail. The function of integrating the Barongsai art community in Payung Sekaki District certainly creates a sense of togetherness that exists between players and spectators, which indicates that there is community integrity in the Barongsai art.